Do cows with stereotypic tongue-rolling behaviour cope better with their environment? - Li, Chenyang; Chen, Xiaoyang; Fang, Tingting; Gu, Xianhong (Frontiers in Veterinary Science, 2024)
Stereotypic behaviours, especially oral stereotypic behaviours, are frequently expressed in farm animals. Tongue-rolling is the most common oral stereotypic behaviour in dairy cows (Bos taurus). If animals frequently display stereotypic behaviours, this is an indication of poor welfare. It has been suggested that animals express stereotypic behaviours as a way of coping with stress. As a result, animals with stereotypic behaviours may have lower levels of stress hormones than animals without stereotypic behaviours. In this study, 916 Holstein cows in the first lactation were subjected to scan sampling behavioural observations 200 times for 10 days. All cows were assigned to either a stereotypic behaviours group (SB) or a control group (CON). The SB group was further subdivided into a tongue-rolling group (TR) and an other-stereotypic behaviours group (OS). The TR group was also split into an only tongue-rolling group (OTR) and a mixed tongue-rolling and other stereotypic behaviours group (TROS). Some cows in the TR group belonged to an extreme tongue-rolling group (ETR). Hair and saliva samples were collected from 601 cows to test cortisol concentrations and dairy herd improvement (DHI) data were collected from a total of 762 cows. There were no differences in hair or saliva cortisol concentrations between the groups (P＞0.05), and the frequencies of tonguerolling were not associated with cortisol concentrations (P＞0.05). For DHI in cows, the milk protein percentage (P=0.028), milk true protein percentage (P=0.021) and milk crude protein percentage (P=0.023) of cows in the ETR group were significantly lower than those in the CON group. For cows in ETR group, as the frequencies of tongue-rolling increased, the milk protein percentage (P=0.034, r=0.365), milk true protein percentage (P=0.022, r=0.393) and milk crude protein percentage (P=0.035, r=0.363) increased. We investigated the relationship between stereotypic behaviours and stress by using a non-invasive sampling method to minimise harm to the cows. We suggest that tongue-rolling may not be a way for cows to cope with stress, at least in terms of cortisol concentrations.